2021
DOI: 10.1111/ctr.14234
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte density is reduced in kidney allografts with high‐risk APOL1 genotypes at transplantation

Abstract: The biology that explains the association of APOL1 variants with nondiabetic kidney diseases in black patients remains controversial.Many, but not all, studies suggest that APOL1 variant-dependent cytotoxicity is associated with kidney diseases (also reviewed in Ref.[1-4]). Furthermore, animal models have linked changes in podocyte number with APOL1 genotype. We previously demonstrated podocyte depletion in transgenic mice constitutively expressing the G2 variant of APOL1 in podocytes under the Nephrin promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, there are data to suggest that podocytes are affected even before clinical disease. 25 While the exact mechanism remains unknown, it is plausible that in high-risk individuals, a second “hit” leads to irrecoverable podocyte drop-out and kidney failure. In the case of membranous nephropathy, the second hit may be immunological.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are data to suggest that podocytes are affected even before clinical disease. 25 While the exact mechanism remains unknown, it is plausible that in high-risk individuals, a second “hit” leads to irrecoverable podocyte drop-out and kidney failure. In the case of membranous nephropathy, the second hit may be immunological.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed no significant effect of recipient APOL1 genotypes on outcomes after DDKT [22]. Other studies assessing DDKT revealed donor APOL1 genotypes and podocyte density underlie more rapid renal allograft failure and development of de-novo collapsing glomerulopathy [23,24]. Results in transplantation provide compelling evidence that kidney APOL1 genotype (and APOL1 expression) contribute to the development of nephropathy.…”
Section: Evidence Supporting Kidney Apol1 Expression In the Developme...mentioning
confidence: 99%
“…20 Kidney donor APOL1 genotypes play a critical role in transplant outcomes. [2][3][4]15 We eagerly await new data to determine the role recipient APOL1 genotypes may play in kidney transplantation. Financial Disclosure: Wake Forest University Health Sciences and Barry Freedman have rights to an issued US patent related to APOL1 genetic testing (www.apol1genetest.com).…”
Section: What Are the Implications For Nephrologists?mentioning
confidence: 99%
“…Recipient race did not associate with risk and the authors concluded donor APOL1 high-risk genotype kidneys associated with a higher incidence of de novo collapsing FSGS after transplant and shorter allograft survival. Recently, Chen et al 15 assessed podocyte density in kidneys from 107 live and deceased African American donors based on APOL1 genotypes. Despite normal kidney function and renal histology at procurement, APOL1 high-risk genotype kidneys had 15% lower podocyte density compared to APOL1 lowrisk genotype kidneys.…”
mentioning
confidence: 99%